2004
DOI: 10.1074/jbc.m311869200
|View full text |Cite
|
Sign up to set email alerts
|

NMR Analysis Shows That a b-Type Variant of Hydrogenobacter thermophilus Cytochrome c552 Retains Its Native Structure

Abstract: Conversion of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 27 publications
2
21
0
Order By: Relevance
“…This information can be used as a guide in assigning the CIDNP spectrum, especially for residues far removed from the heme centre in the case of the holo proteins. The assignment of the observed resonances can be made by reference to the static accessibility data and by comparison with chemical shift assignments obtained from three-dimensional (3D) 15 N-edited TOCSY-HSQC and NOESY-HSQC experiments on 15 N-labelled reduced state holo C10A/C13A protein [17] and the wild-type c 552 [13]. These 3D NMR experiments have enabled the backbone amide protons and the indole NH protons of the tryptophan residues to be assigned.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This information can be used as a guide in assigning the CIDNP spectrum, especially for residues far removed from the heme centre in the case of the holo proteins. The assignment of the observed resonances can be made by reference to the static accessibility data and by comparison with chemical shift assignments obtained from three-dimensional (3D) 15 N-edited TOCSY-HSQC and NOESY-HSQC experiments on 15 N-labelled reduced state holo C10A/C13A protein [17] and the wild-type c 552 [13]. These 3D NMR experiments have enabled the backbone amide protons and the indole NH protons of the tryptophan residues to be assigned.…”
Section: Resultsmentioning
confidence: 99%
“…The apo state of the protein is characterised by a decrease in helicity of 29% and an increase of 8.5% in the hydrodynamic radius, with respect to the holo form of the C10A/C13A mutant [16]. Both of these points and evidence from NMR spectroscopy [16,17] show that the apo state of the mutant can be characterised as a partially folded species with some molten-globule like characteristics which undergoes conformational fluctuations on a millisecond timescale. These observations are in close agreement with a similar investigation of the differences between the apo and holo forms of both cytochrome c [19] and myoglobin [20].…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…In our previous work, we have reported the first in vitro formation of a c-type cytochrome containing two thioether bonds (4). It was shown that these bonds can form stereoselectively in vitro (5), presumably by forming a b-type cytochrome intermediate with the heme in one stereoisomeric orientation relative to its ␣,␥-mesoaxis (6). Some aspects of the heme orientation during the in vitro formation of c-type cytochromes have been discussed previously (7).…”
mentioning
confidence: 99%